First report on the pathotype diversity of Phytophthora sojae in Manitoba, Canada. (November 2020) - Henriquez, M.A.; Kim, Y.M.; McLaren, D.L.; Conner, R.L.; Xue, A.; Marchand, G.; Yu, K.; Chang, K.F.; Hwang, S.F.; Strelkov, S.E.; Gossen, B.D.
Abstract: Phytophthora root and stem rot of soybean is caused by the oomycete pathogen Phytophthora sojae, which can infect plants at all stages of growth when soil conditions favour pathogen development. In Manitoba, the acreage of commercial soybean has increased dramatically in recent years. Root and stem rot caused by P. sojae was first detected in commercial soybean in Manitoba in 2011. The objectives of this study were to characterize the pathotype diversity of P. sojae infecting common soybean varieties in Manitoba and identify Rps genes effective against this population. Forty-four, 77 and 89 soybean fields located in the major production areas in Manitoba were surveyed in 2014, 2016 and 2017, respectively. Pathogen collections of 32 (2014), 34 (2016) and 35 (2017) isolates were made each year and evaluated for pathotype classification. Pathotypes of P. sojae were identified based on the pattern of their reactions on a differential set, which included the Rps genes 1a, 1b, 1c, 1d, 1k, 3a, 6 and 7 . The most common pathotype was 1a, 1c, 7 (race 4), which comprised 45% of the 101 isolates examined, followed by the pathotypes 1a, 1b, 1c, 1k, 7 (race 25) and 1a, 1b, 1k, 7 (race 28), comprising 34% and 11% of the isolates, respectively. The resistance genes Rps1c and 1k are the most common genes deployed in Manitoba. Based on the results of this study, stacking of resistance genes Rps1d, Rps3a and Rps6 in soybean cultivars targeted for deployment in Manitoba would prove useful in reducing the severity of Phytophthora root and stem rot. Highlights: Pathotype diversity of Phytophthora sojae assessed for the first time in Manitoba. The predominant pathotype in Manitoba was 1a, 1c, 7 (race 4). Common pathotypes in Manitoba were 1a, 1b, 1c, 1k, 7 and 1a, 1b, 1k, 7. The best Rps genes to deploy in Manitoba are Rps1d, Rps3a and Rps6.